ANALISIS YURIDIS TERHADAP PENERIMAAN PATEN PUBLIC DOMAIN PEMBUNGKUS BERGELEMBUNG YANG DI PATENKAN KEMBALI DI INDONESIA (STUDI PUTUSAN NOMOR 44/PDT.SUS-PATEN/2020/PN.NIAGA.JKT.PST): Juridical Analysis of The Acceptance of Public Domain Patents of Bubbly Wrappers Re-Patented in Indonesia (Study Decision Number 44/Pdt. SUS-Patent/2020/Pn. Trade. Jkt. Pst - Shirley Natasha; Simona Bustani (AMICUS CURIAE, 2024)
Patents are exclusive rights that the state grants to inventors based on the results of inventions carried out by themselves or approves other parties to do it in the field of technology within a certain period of time. The formulation of the problem is whether a simple patent for a simple colored bubble wrap which has become a public domain in the United States has the novelty to be registered in Indonesia and what is the decision of a commercial court judge in a simple patent dispute regarding the public domain in Decision Number 44/Pdt.Sus-Paten/2020/ PN.Niaga.Jkt.Pst based on Law no. 13 of 2016 concerning Patents. This research is a normative legal research type through the use of secondary data, which is supported by primary data. The nature of research is descriptive analysis, with qualitative analysis of the data. Based on the conclusion that patents that have been registered when viewed from Article 132 Law No. 13 of 2016 concerning patents can be canceled or abolished and the decision of the panel of judges at the commercial court is considered to be inappropriate in its considerations regarding the non-fulfillment of the element of novelty because it has not been careful with the existing problems and facts. In this case the judge should have been more observant in considering the provisions formulated by the Patent Law.